Selective list of the Catalogues of the VIR Global Collection on vegetables and cucurbits published in 1962–2023 - Editorial Article (Труды по прикладной ботанике, генетике и селекции)
The Catalogue of the VIR Global Collection series is addressed to plant breeders and crop experts solving practical problems in plan breeding and seed production, plant scientists conducting fundamental and applied research, teachers and learners. The publications within this series help to disclose the potential of the VIR global collection of plant genetic resources and the VIR herbarium (WIR) as an important part of Russian bioresource collections (BRC). The editors of the journal Proceedings on Applied Botany, Genetics and Breeding decided to publish the Selective list of the Catalogues of the VIR Global Collection on vegetables and cucurbits published in 1962–2023 to throw light on VIR’s publishing activities, attract more attention to the Catalogue of the VIR Global Collection series, and specify the numbers and titles of the series’ issues for authors of scientific manuscripts. For the users’ convenience, the sources are arranged chronologically, following the order of issue numbers. The editors hope that this list will prove useful to our readers and authors.